Knowledge, awareness, and attitude among pharmacists regarding the risk estimation of cardiovascular disease in Jordan: Immersion of lipid-lowering agents - Abeer M. Rababa'h; Mera Ababneh; Nour N. Abedalqader; Salah Eldien Altarabsheh (Heliyon, 2023)
The Risk Estimation of Cardiovascular Disease (CVD) is an important factor for predicting the incidence of cardiovascular events in a given population. This study aimed to assess the knowledge, awareness, and attitude of pharmacists in Jordan regarding the risk estimation of CVD and the use of lipid-lowering agents. The study is particularly interested in investigating the extent to which pharmacists are immersed in this area of practice, which can significantly impact patient health outcomes. The study employed a cross-sectional design, with a sample of pharmacists drawn from various regions in Jordan. Data were collected through a self-administered questionnaire, which was designed to explore pharmacists' knowledge of CVD risk estimation tools and their awareness of lipid-lowering agents' efficacy and side effects. The questionnaire also assessed pharmacists' attitudes towards the use of these agents in practice and their perceptions of the barriers to implementing CVD risk estimation tools. The study's findings shed light on the suboptimal levels of overall knowledge score of pharmacists in Jordan regarding CVD risk estimation and lipid-lowering agents' use. The results provided insights into the gaps that exist in pharmacists' knowledge and practice and help to identify areas for improvement. Ultimately, the present findings inform strategies to enhance pharmacists' engagement in CVD risk estimation and improve patient outcomes in Jordan and highlight the urgent need for ongoing education and training for pharmacists to improve their knowledge and skills in managing patients with dyslipidemia.